2003
DOI: 10.1161/01.hyp.0000092441.27668.bd
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Stimulated Hydrogen Peroxide Increases Guanylate Cyclase Activity in Vascular Smooth Muscle

Abstract: Abstract-Insulin resistance is associated with vascular disease. Physiological concentrations of insulin inhibit cultured vascular smooth muscle cell (VSMC) contraction and migration by increasing nitric oxide (NO)-stimulated cGMP accumulation. The failure to do so in insulin-resistant states may aggravate vascular disease. We sought to determine the mechanism of insulin's increase in cGMP accumulation. Isobutylmethylxanthine, an inhibitor of phosphodiesterase activity, inhibited the decline in cGMP levels mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
5
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 39 publications
2
5
0
Order By: Relevance
“…H 2 O 2 is a stable component of reactive oxygen species in VSMCs and is also a second messenger for various stimulators in smooth muscle cells (44). The current study demonstrated that high-dose insulin could induce a release of H 2 O 2 , which is consistent with the conclusions drawn from previous studies (45). In addition, the inhibition of GJIC function by H 2 O 2 through the induction of Cx43 phosphorylation has been verified in various types of cells (46,47).…”
Section: Discussionsupporting
confidence: 91%
“…H 2 O 2 is a stable component of reactive oxygen species in VSMCs and is also a second messenger for various stimulators in smooth muscle cells (44). The current study demonstrated that high-dose insulin could induce a release of H 2 O 2 , which is consistent with the conclusions drawn from previous studies (45). In addition, the inhibition of GJIC function by H 2 O 2 through the induction of Cx43 phosphorylation has been verified in various types of cells (46,47).…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with this interpretation, H 2 O 2 was not able to increase cGMP levels in endothelium-denuded arteries. In agreement with our observations, previous studies have reported that in vascular smooth muscle cells(54) or in endothelium-denuded arteries (23), H 2 O 2 did not affect the production of cGMP, again suggesting that the presence of an intact endothelium is required for H 2 O 2 to increase cGMP.…”
supporting
confidence: 93%
“…In previous studies, ROS (specifically hydrogen peroxide, H 2 O 2 ) increased NO-induced cGMP activity. 54 We demonstrated that PHD plasma-produced NO enhanced endothelial cell proliferation and migration but not tube formation. However, these studies are not without limitations.…”
Section: Discussionmentioning
confidence: 73%